1999
DOI: 10.1001/archneur.56.8.997
|View full text |Cite
|
Sign up to set email alerts
|

A Positron Emission Tomographic Study of Subthalamic Nucleus Stimulation in Parkinson Disease

Abstract: Stimulation of the STN reduces the movement-related impairment of frontal motor association areas and the inappropriate motor cortex resting activity in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(52 citation statements)
references
References 28 publications
7
41
1
Order By: Relevance
“…This finding underlines the restoration of a more physiological frontal-striatal-thalamic circuit by STN stimulation although the precise mechanims of such stimulation remains debated [4]. This effect may be explained by an improved functioning of the thalamocortical excitatory pathway and is in accordance with recent studies [7,27].…”
Section: Effects Of Stn Stimulation On Motor Execution Activation Prosupporting
confidence: 86%
See 2 more Smart Citations
“…This finding underlines the restoration of a more physiological frontal-striatal-thalamic circuit by STN stimulation although the precise mechanims of such stimulation remains debated [4]. This effect may be explained by an improved functioning of the thalamocortical excitatory pathway and is in accordance with recent studies [7,27].…”
Section: Effects Of Stn Stimulation On Motor Execution Activation Prosupporting
confidence: 86%
“…Interestingly the overactivation observed in the right DLPFC (i. e. controlateral to the stimulation and ispilateral to the movement) has also been found by Ceballos-Baumann et al [7]. In a recent PET study, the right DLPFC, and not the left one, appeared hypoactivated, compared with controls, while PD patients performed a joystick motor task in freely selected directions with the right hand [40].…”
Section: Effects Of Stn Stimulation On Motor Execution Activation Prosupporting
confidence: 70%
See 1 more Smart Citation
“…The decrease in cerebral blood flow in the supplementary motor area has been correlated with the improvement of rigidity [13]. However, some investigations indicated that during motor execution, STN DBS induced an increased activation of the supplementary motor area [14,15,16]. The inconsistency might originate from the heterogeneity of patients enrolled in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies assessing the neural changes induced by DBS during a motor task have revealed an activation of the areas involved in kinesis, i.e. supplementary motor area (SMA), dorsolateral prefrontal cortex (DLPFC) and anterior-cingulate cortex (ACC) and a deactivation of the so-called ' accessory ' pathways (Ceballos-Baumann et al, 1999;Grafton et al, 2006;Limousin et al, 1997;Strafella et al, 2003;Thobois et al, 2002).…”
Section: Imaging Motor Effects Of Deep Brain Stimulationmentioning
confidence: 99%